SDR42E1 modulates vitamin D absorption and cancer pathogenesis: insights from an in vitro model - Hendi, Nagham Nafiz; Nemer, Georges (Frontiers in Endocrinology, 2025)
IntroductionVitamin D is a pleiotropic hormone essential for bone health and overall physiological function. Despite its significance, vitamin D deficiency remains widespread and is often influenced by genetic factors. MethodsThis study investigates the role of SDR42E1, a gene encoding a short-chain dehydrogenase/reductase enzyme, in vitamin D regulation and sterol metabolism. Using CRISPR/Cas9 gene-editing, we generated an SDR42E1 knock-in model in HCT116 colorectal cells, which exhibit high endogenous SDR42E1 expression, harboring a nonsense variant associated with vitamin D deficiency.ResultsIntegrated transcriptomic and proteomic analyses revealed significant dysregulation of sterol absorption and metabolism (fold change (FC) = 1.8, P = 0.007) and cancer-related signaling pathways (FC = −1.7, P = 0.02). Notably, key differentially expressed genes included upregulated LRP1B and ABCC2, alongside downregulated WNT16 and SLC7A5. Proteomic profiling confirmed alterations in cell proliferation-related proteins, including reduced ALDOA expression (FC = −0.37, P = 0.0005). Functionally, SDR42E1 deficiency reduced cell viability by 53% (P = 0.0001), an effect reversed by transient SDR42E1 overexpression with restoring ABCC2 expression. ConclusionThese findings establish SDR42E1 as a key modulator of vitamin D-related pathways and highlight its potential as a therapeutic target for addressing vitamin D deficiency and associated pathologies, including cancer.